Pesan Kemanusiaan dalam Pembukaan FIFA World Qatar 2022 - Najla Amaly; Yasir Adenan (Al-Hiwar : Jurnal Ilmu dan Teknik Dakwah, 2023)
World issues regarding the occurrence of cases of war between countries were so rife in 2022 ago. Starting from the cases of Ukraine and Russia or the cases of Israel and Palestine. Many other countries have shown their support for peace and an end to wars between countries. 2022 is the year FIFA World will be held in Qatar. On this occasion Qatar took part in conveying a message of unity and humanity in the opening of the event. Ghanim Muftah, a Muslim and disabled person, was chosen with Morgan Freeman, an American actor. The interaction of these two figures conveys that even though humans have different backgrounds, they can live peacefully in this world. The purpose of this research is to analyze the content of the messages conveyed at the opening of FIFA World 2022. The method uses qualitative content analysis. The result of this research is that the opening of FIFA World Qatar 2022 has a message of tolerance, diversity and unity